Pleuropulmonary blastoma: a report from the TREP (Tumori Rari in Età Pediatrica) Project. Issue 2 (April 2020) - Grigoletto, Veronica; Tagarelli, Arianna; Atzeni, Catia; Cecchetto, Giovanni; Indolfi, Paolo; De Pasquale, Maria Debora; De Leonardis, Francesco; Coppadoro, Beatrice; Sorbara, Silvia; Chiaravalli, Stefano; Ferrari, Andrea; Bisogno, Gianni
Introduction: Pleuropulmonary blastoma (PPB) is a rare, aggressive mesenchymal tumor of childhood. The Italian Tumori Rari in Età Pediatrica (TREP) Registry was the first in Europe dedicated to prospective data collection on rare pediatric tumors. We analyzed data from an Italian series of patients with PPB, focusing on the role of the TREP Project. Methods: We considered patients aged 0–14 with histologically confirmed diagnosis, registered in population-based cancer registries (before 2000) or the TREP Registry (2000 to 2014), and analyzed data on clinical characteristics, treatment, and outcome. Event-free survival (EFS) and overall survival (OS) were estimated. Relevant prognostic factors were identified performing a univariate analysis. Results: Thirty-seven cases were included (7 type I, 13 type II, 17 type III). The average diagnosis rate rose from 1.10 to 1.73 cases/year after the TREP Project started. All patients underwent surgery, 33 received chemotherapy, and 9 had radiotherapy. The median follow-up was 8.7 years. For type I, II, and III, respectively, the 5-year OS was 85.7% (33.4–97.9), 52.7% (23.4–75.5), and 57.8% (31.1–77.3); the 5-year EFS was 85.7% (33.4–97.9), 52.7% (23.4–75.5), and 52.9% (27.6–73.0). Favorable prognostic factors for EFS were Intergroup Rhabdomyosarcoma Study (IRS) stage I ( p = 0.03) and T1 tumor ( p = 0.05). A total of 78.3% of patients who had chemotherapy after 2000 received a standardized treatment. Conclusions: The TREP Registry showed an excellent capacity for registering cases of PPB. Patients received homogeneous treatment after the TREP Project started. Long-term outcomes were excellent for type I and unsatisfactory for type II and III. Tumor invasiveness and IRS stage were of prognostic value.